2022
DOI: 10.3390/cancers14174212
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Landscape Alterations in Primary Tumor and Matched Lymph Node Metastasis in Hormone-Naïve Prostate Cancer Patients

Abstract: Background: Prostate cancer (PCa) is a disease with a wide range of clinical manifestations. Up to the present date, the genetic understanding of patients with favorable or unfavorable prognosis is gaining interest for giving the appropriate tailored treatment. We aimed to investigate genetic changes associated with lymph node metastasis in a cohort of hormone-naïve Pca patients. Methods: We retrospectively analyzed data from 470 patients who underwent surgery for PCa between 2010 and 2020 at the Department of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…CD8A (38), FCGR3A (39) and PTPRC (40) are identi ed as candidate biomarkers in various cancers or important molecule in PCa patients with bone metastases. Recent studies have indicated that HRAS alterations in patients with PCa lymph node metastasis demonstrated worse overall survival and disease free survival (41). Further studies are still needed to determine how these hub genes contribute to PCa bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…CD8A (38), FCGR3A (39) and PTPRC (40) are identi ed as candidate biomarkers in various cancers or important molecule in PCa patients with bone metastases. Recent studies have indicated that HRAS alterations in patients with PCa lymph node metastasis demonstrated worse overall survival and disease free survival (41). Further studies are still needed to determine how these hub genes contribute to PCa bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described, through different biochemical pathways, a possible association between metabolic alterations, systemic inflammation related to metabolism, and the incidence of prostate cancer [ 63 , 64 ]. However, other factors involved in prostate cancer development, such as genetics and epigenetics [ 65 , 66 , 67 , 68 ], have been hypothesized to play a role and should be controlled for further. Overall, although the exact mechanism remains to be elucidated, there is a substantial rationale for the association between dietary factors and prostate cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…CD8A [38], FCGR3A [39], and PTPRC [40] are identified as candidate biomarkers in various cancers or important molecules in PCa patients with bone metastases. Recent studies have indicated that HRAS alterations in patients with PCa lymph node metastasis demonstrated worse overall survival and disease-free survival [41]. Further studies are still needed to determine how these hub genes contribute to PCa bone metastases.…”
Section: Discussionmentioning
confidence: 99%